Project “Osprey in Russia”: key findings in 2019–2023 - Miroslav V. Babushkin; Andrey V. Kuznetsov; Alexey A. Sharov; Vasily G. Pchelintsev; Urmas Sellis; Gunnar Sein; Elena A. Shikalova; Irina G. Utekhina; Albert V. Bragin; Pavel A. Futoran; Evgeniy V. Kholodov; María Del Mar Delgado (Пернатые хищники и их охрана)
In Russia, Osprey (Pandion haliaetus) nests from the western borders of the Kaliningrad region to the Kamchatka Peninsula, Anadyr River basin, Sakhalin Island, southern Kuril Islands, and Japan. The northern border of its distribution runs along the edge of the northern taiga, forested river valleys in the north. During the Project, the breeding population, migration routes, and wintering sites were determined for the first time for Ospreys inhabiting the north of the European part of Russia, south of Central Siberia (Sayano-Shushenski State Nature Reserve), and in Far East (“Magadan” State Nature Reserve, central part of the Kamchatka Peninsula). After a significant population reduction because of “harmful predators” control and the use of organochlorine pesticides (until the 1970s), Osprey population stabilizes and gradually grows (2–2.5 times in about 30 years) in most regions of the European part of Russia. I